Marginal Integrity of Class-I Restorations, Restored with Amalgam and Bonded Amalgam; A Comparative Study - Rana, Muzammil Jamil Ahmed; Rana, Mehmood Ahmed; Bano, Sara; Bangash, Ajmal Yousaf; Islam, Sadaf; Hamdani, Sara (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the marginal integrity of Class-I amalgam and bonded amalgam restorations in maxillary and mandibular molars at seven days, three, six and twelve-months intervals. Study Design: Comparative prospective study. Place and Duration of Study: Department of Operative Dentistry, Armed Forces Institute of Dentistry, Rawalpindi Pakistan,from Jul 2017 to Jul 2018. Methodology: A total number of 114 patients of either gender with an age range of 14-45 years having Class-I cavities in first and second maxillary and mandibular molars on both sides were equally distributed in two groups. Group-A received conventional Amalgam, and Group-B received bonded amalgam restorations. All the fillings were placed and carved using routine instruments used for amalgam restorations, and the restorations were polished after 24 hours. The patients were initially evaluated for marginal ditching around restorations with the help of a dental mirror and explorer at seven days,followed by inspection at 3, 6 and 12 months. Results: Of the 114 participants, all showed excellent marginal integrity at seven-days intervals regardless of the restorative material used. However, marginal integrity deteriorated swiftly with time among those 57(50%) participants who acquired conventional Amalgam. Marginal integrity at 3, 6 and 12-months period was 51(89.5%), 35(61.4%) and 17(29.8%), respectively.Bonded amalgam restorations performed superiorly with 100%, 56(98.2%) and 43(75.4%) successful marginal integrity at 3, 6 and 12-months, respectively. Conclusion: Bonded amalgams can be a better substitute than non-bonded amalgam restorations with superior longevity in marginal integrity. Keywords: Amalgam, Bonded amalgam, Marginal integrity, Micro-leakage, Marginal deterioration, Restoration longevity.